Thermodynamic analysis of biochar produced from groundnut shell through slow pyrolysis - Nikhil Rathod; Sudhir Jain; Maga Ram Patel (Energy Nexus, 2023)
The current study centred on the energetic and exergetic analysis of a specially designed continuous biochar production system that works on slow pyrolysis technology and is capable of creating biochar constantly from agricultural leftovers. In this investigation, a groundnut shell with a lower heating value (LHV) of 13.35 MJ/kg was selected as a feedstock. It was converted into biochar using a slow pyrolysis technique at 400 °C, 450 °C, and 500 °C for 4 min of residence period. Biochar yield, bio-oil yield, and syngas yield were found in the range between 16.83–30.5%, 24.36–27.56%, and 45.14–55.61%, respectively at different pyrolysis temperatures. The LHV of biochar and bio-oil was found maximum of 23.55 MJ/kg and 23.12 MJ/kg at 500 °C respectively. Syngas heating value increased from 7.19 to 7.72 MJ/Nm3. The energy efficiency of the system ranged from 80.22% to 84.29%, while exergy efficiency ranged from 76.37% to 79.29%, with the maximum achieved at 400 °C.